2019
DOI: 10.1371/journal.pone.0213769
|View full text |Cite
|
Sign up to set email alerts
|

Presence and function of stress granules in atrial fibrillation

Abstract: Aims Stress granules (SGs) are transient cytoplasmic mRNA and protein complexes that form in eukaryotic cells under stress. SGs are related to multiple diseases, but there are no reports of the existence of SGs in atrial fibrillation (AF). Methods and results Cell models of AF were established by field stimulation at 600 times per minute. HL-1 cells, cardiomyocytes and cardiac fibroblasts were transfected with G3BP1-cDNA plasmid by Lipofectamine 2000. The presence of SG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Nevertheless, all discovered multifunctional RBPs are ubiquitously expressed across human tissues, suggesting that these proteins are major players in RNA transcriptional and translational regulation, contributing to both global and cell-line or tissue-specific manifestations. For instance, this appears to be the case for G3BP1 - a known multi-functional RBP that can selectively compartmentalize specific sets of mRNAs to stress granules, in order to reprogram mRNA translation under certain global stress conditions (Matsuki et al, 2013; Ying & Khaperskyy, 2021; Sahoo et al, 2018), as well as tissue-specific contexts such as atrial fibrillation in heart (Dong et al, 2019). Additionally, G3BP1 plays an important role in DNA/RNA unwinding (Costa et al, 1999) and binds to specific RNA stem-loop structures to trigger mRNA degradation (Fischer et al, 2020), which is essential for maternal mRNA clearance (Laver et al, 2020)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, all discovered multifunctional RBPs are ubiquitously expressed across human tissues, suggesting that these proteins are major players in RNA transcriptional and translational regulation, contributing to both global and cell-line or tissue-specific manifestations. For instance, this appears to be the case for G3BP1 - a known multi-functional RBP that can selectively compartmentalize specific sets of mRNAs to stress granules, in order to reprogram mRNA translation under certain global stress conditions (Matsuki et al, 2013; Ying & Khaperskyy, 2021; Sahoo et al, 2018), as well as tissue-specific contexts such as atrial fibrillation in heart (Dong et al, 2019). Additionally, G3BP1 plays an important role in DNA/RNA unwinding (Costa et al, 1999) and binds to specific RNA stem-loop structures to trigger mRNA degradation (Fischer et al, 2020), which is essential for maternal mRNA clearance (Laver et al, 2020)).…”
Section: Discussionmentioning
confidence: 99%
“…Dual-or multiprotein functionality can be achieved through context-specific differences in subcellular localization (Buchan, 2014), interaction partners (Cirillo et al, 2020;Yang et al, 2019), or the presence of multiple RNA-binding domains (Müller-McNicoll & Neugebauer, 2013) -all of which can fine tune or restrict the subset of recognized target genes. Based on published immunofluorescence imaging-based evidence of subcellular RBP localization (Van Nostrand et al, 2020), 13 out of 21 multifunctional RBPs indeed localized equally well to both nucleus and cytosol, suggesting functionality in both compartments (Table S3).…”
Section: Differential Affinity Of Multifunctional Rbps For Cds Lengths and 5' Utr Structuresmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most common arrhythmia in clinical practice, in which chronic inflammatory response and oxidative stress play an important role. It has been confirmed that SGs exist in atrial myocytes of AF and can reduce ROS and calcium overload levels 144 . However, whether SGs can fight against apoptosis and fibrosis, thus reducing the AF incidence, remains unknown.…”
Section: Stress Granules Involving In Biological Disordersmentioning
confidence: 99%
“…It has been confirmed that SGs exist in atrial myocytes of AF and can reduce ROS and calcium overload levels. 144 However, whether SGs can fight against apoptosis and fibrosis, thus reducing the AF incidence, remains unknown. Consequently, it is of great significance to further reveal the aetiology and potential therapeutic targets of AF (Figure 3 ).…”
Section: Stress Granules Involving In Biological Disordersmentioning
confidence: 99%
“…SGs are also associated with several other diseases, such as atrial fibrillation, organ fibrosis, autoimmune disease and brain ischemia [ 75 ]. It is expected that more diseases will be linked with SGs soon.…”
Section: Sgs and Human Diseasesmentioning
confidence: 99%